Auctions with Frictions: Recruitment, Entry, and Limited Commitment - Lauermann, Stephan; Wolinsky, Asher (Review of Economic Studies, 2026)
Abstract Auction models are convenient abstractions of informal price-formation processes that arise in markets for assets or services. These processes involve frictions like bidder recruitment costs for sellers, participation costs for bidders, and limitations on sellers’ commitment abilities. This paper develops an auction model that captures such frictions. We derive novel insights, notably that outcomes are often inefficient, that markets sometimes unravel, and that the observability of competition may have a large effect.